New public management and the extension of police control: community safety and security networks in Canada - Sanders, Carrie B. (Policing and society, 2019)
There are growing discussions regarding the need for collaborative responses for the provision of community safety, such that crime prevention efforts include the partnering of police with various community organisations and social services. In this article, we ethnographically examine one such development in Canada - community Situation Tables - to better understand the processes by which security networks are developed, implemented and governed. We argue that the managerial measures introduced to govern Situation Tables work as a technology of social control that redistributes responsibility for community safety and risk mitigation onto organisations and the clients they serve. Situation Tables, we argue, operate as if they are neutral entities. However, by looking at the mentalities, political and economic contexts of their development, implementation and governance identifies how they are influenced and shaped by traditional policing practices, which if not attended to carefully, can evade democratic accountability.